2017
DOI: 10.1016/j.arthro.2017.01.041
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Dynamic Graft Bending Angle in Anterior Cruciate Ligament–Reconstructed Knees During Downward Running and Level Walking: Comparison of Flexible and Rigid Drills for Transportal Technique

Abstract: Purpose To determine in vivo dynamic graft bending angle (GBA) in anterior cruciate ligament (ACL) reconstructed knees, correlate the angle to tunnel positions and tunnel widening, and evaluate the effects of two femoral tunnel drilling techniques on GBA. Methods Patients with an isolated ACL injury undergoing reconstruction were included from 2011 to 2012. Trans-portal techniques were used to create femoral tunnels. Tunnel locations were determined using 3D-CT. Tibio-femoral kinematics during treadmill walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 66 publications
0
46
1
Order By: Relevance
“…First, the femoral tunnel was drilled with the knee at maximal flexion in our cohort, which might have resulted in a more posterior femoral tunnel exit. 28,29 Because it has been reported that a more posterior femoral tunnel exit correlates with a smaller GBA, our surgical technique might have contributed to low GBA values. 29 Second, the GBA and bone tunnel were measured on 3D MRI based on the graft axis in this study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…First, the femoral tunnel was drilled with the knee at maximal flexion in our cohort, which might have resulted in a more posterior femoral tunnel exit. 28,29 Because it has been reported that a more posterior femoral tunnel exit correlates with a smaller GBA, our surgical technique might have contributed to low GBA values. 29 Second, the GBA and bone tunnel were measured on 3D MRI based on the graft axis in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Severe femoral tunnel widening may result in impairment of graft incorporation, joint laxity, and complications in revision surgery. 1,23 Tashiro et al 28 used a quadriceps tendon autograft with a bone block in ACLR, and they demonstrated that a higher GBA moderately correlated with greater tunnel widening. Segawa et al 22 reported that a higher GBA may increase mechanical stress on the anterior margin of the femoral tunnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that the magnitude of the graft bending angle seen with AM portal tunnels results in a 2- to 3-fold increase in graft strain at the femoral tunnel aperture, producing increased graft signaling on postoperative magnetic resonance imaging. 12,21,34,35…”
Section: Discussionmentioning
confidence: 99%
“…This makes graft passage more tedious, increases graft forces at the tunnel aperture, and may negatively affect graft healing. 5,12,34,35…”
mentioning
confidence: 99%